BioUniWA – WEB SERVICES GENERATION SYSTEM AND PIPELINES FOR UNIFIED ACCESS TO RESOURCES IN THE FIELD OF BIOINFORMATICS - E. G. Komyshev; M. A. Genaev; K. V. Gunbin; D. A. Afonnikov (Вавиловский журнал генетики и селекции, 2015)
We present the BioUniWA system for automatic generation of web services for unified access to resources in the field of bioinformatics. The BioUniWA system was originally designed as the BioInfoWF development system to support access to computing modules and pipelines through web services. BioUniWA can automatically generate web-based applications for computational modules and pipelines whose formal descriptions are defined by a language based on XML. In the future, one will be able to use these web-based applications in a variety of bioinformational systems, such as Taverna or Galaxy, as well as directly in the source code of applications to be developed. We have designed a tool that greatly simplifies the annotation of computing modules and schemes of pipelines, as well as their publication via Internet.BioUniWA is distributed under a free GNU general public license. The distribution package and user documentation are available at BioUniWA http://bioinfowf.bionet.nsc.ru.